Controllable mixed-charged co-assembly of dendritic lipopeptides into invisible capsid-like nanoparticles as potential drug carriers. Issue 39 (19th April 2021) - Xu, Qinhan; Shu, Chang; Li, Yachao; Zhuang, Rong; Jiang, Lei; Xu, Xianghui
Abstract : A new type of molecular and supramolecular strategy is proposed to controllably construct mixed-charged nanoparticles with resistance to protein adsorption. Abstract : The feature of invisibility is vital in drug nanocarriers for prolonging blood transportation, with this generating excellent resistance to protein adsorption and clearance from the body. In this work, we report a well-designed molecular and supramolecular strategy for precisely developing mixed-charged nanoparticles with resistance to protein adsorption. We constructed anionic dendritic lipopeptides (ADLs) and cationic dendritic lipopeptides (CDLs) with eight carboxyl or amino groups as terminal groups. By regulating the molar ratio between ADLs and CDLs, amphiphilic dendritic lipopeptides were assembled into nanoparticles (NPs) with adjustable surface charge. Notably, the co-assembly of equivalent amounts of ADLs and CDLs generated neutral mixed-charged NPs as invisible capsid-like NPs (ICNPs). ICNPs were able to resist protein adsorption and serve as stealth nanocarriers for harboring guest molecules.